SINKRETISME DALAM NASKAH SASTRA MISTIK - Roch Aris Hidayat (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2018)
This study aims to reveal the values of syncretism in the text of Sastra Mistik (Mystic Literature). This manuscript was found and stored in the Museum Lambung Mangkurat of South Kalimantan Province. This study was conducted with a philological approach. The scope of this study consists of codicology and texture, but the focus of this study is on texture. The method used consisted of identification of manuscripts, transliteration of manuscripts, manuscript descriptions, and content analysis. The results of the study of the contents of the manuscript states that the text of Sastra Mistik contains the deeds of prayer or human plea to God Almighty. In addition, the text of Sastra Mistik also contains human appeals to God's creatures that are considered to have transcendent powers, especially jinns. The human relationship with God and the jinn in Sastra Mistik is manifested in a variety of attitudes and behaviors. The mystical attitudes and behaviors shown in Sastra Mistik are the social realities that flourished among Banjar communities in the past.